Anti-beta-2 glycoprotein I epitope specificity: from experimental models to diagnostic tools. (July 2016) - Meroni, P L
Beta-2 glycoprotein I (β2GPI) is the main antigenic target for anti-phospholipid antibodies (aPL), the serological markers of anti-phospholipid syndrome (APS). Conformational changes of the molecule seem to be essential for exposing the cryptic epitope for aPL binding and to trigger pathogenic pathways. There is increasing evidence that a conformational epitope located in the Domain I (DI) of the molecule is the main epitope targeted by human autoantibodies. The pathogenic role of the DI epitope has been recently supported by in vivo models and by immuno-histopathological findings in APS patients. Antibodies targeting β2GPI-DI are more frequently detected in patients with full-blown APS compared to asymptomatic aPL carriers or patients with infectious diseases who have antibodies directed against the whole molecule. Anti-DI antibodies are positively correlated with medium to high titres of aPL, with the presence of lupus anticoagulant and thrombotic and pregnancy manifestations, enabling identification of patients at higher risk of clinical events. However, some APS patients develop antibodies reacting against β2GPI epitopes other than DI, suggesting that other anti-β2GPI antibody subsets may be clinically relevant. Although preliminary results suggest that anti-DI antibodies can be detected by different assays in a comparable manner, further prospective studies are needed to support their use in the clinical setting and their predictive value.